2022
DOI: 10.3390/jcm11030788
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Changes in the Oxyhemoglobin Dissociation Curve of Critically Ill COVID-19 Patients

Abstract: Critical COVID-19 is a life-threatening disease characterized by severe hypoxemia with complex pathophysiological mechanisms that are not yet completely understood. A pathological shift in the oxyhemoglobin curve (ODC) was previously described through the analysis of p50, intended as the oxygen tension at which hemoglobin is saturated by oxygen at 50%. The aim of this study was to analyze Hb-O2 affinity features over time in a cohort of critically ill COVID-19 patients, through the analysis of ODC p50 behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
18
2
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 34 publications
1
18
2
1
Order By: Relevance
“…This would show up as a left shift in the oxyhaemoglobin dissociation curve (ODC), in particular a reduction in p50, the value of p a O 2 at 50% saturation of haemoglobin with O 2. 4 However, of the few, small studies of the affinity of oxygen for Hb in patients with COVID‐19, 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 only two found increased affinity of Hb for oxygen. 6 , 12 Suspecting that the discrepancies might be due not only to small study size but also to the inclusion of patients receiving treatment (oxygen therapy, bronchodilators, fluid therapy, corticoids, intensive care, etc.…”
Section: Introductionmentioning
confidence: 99%
“…This would show up as a left shift in the oxyhaemoglobin dissociation curve (ODC), in particular a reduction in p50, the value of p a O 2 at 50% saturation of haemoglobin with O 2. 4 However, of the few, small studies of the affinity of oxygen for Hb in patients with COVID‐19, 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 only two found increased affinity of Hb for oxygen. 6 , 12 Suspecting that the discrepancies might be due not only to small study size but also to the inclusion of patients receiving treatment (oxygen therapy, bronchodilators, fluid therapy, corticoids, intensive care, etc.…”
Section: Introductionmentioning
confidence: 99%
“…We would like to thank Böning et al for all the important issues raised in the present commentary [ 1 ], giving us the possibility to review all our data and to discuss in more detail this emerging, interesting topic. In line with what was reported by Vogel et al [ 2 ], we found a left shift in Oxygen-Hemoglobin Dissociation (ODC) curve affinity, measured throughout a p50 ODC curve analysis, but only in the first 3 days of the Intensive Care Unit (ICU) stay (p50 early), compared with the last 3 days (p50 late; 26.1 ± 4.7 mmHg, p < 0.01 vs. 26.2 mmHg ± 7.0 mmHg, p = 0.13) [ 3 ].…”
mentioning
confidence: 99%
“…As explained in the original paper [ 3 ], due to the retrospective nature of the study, in vivo measurements of 2,3-BPG were not performed, so this correction in the formula was not used; we have therefore set it as a fixed value at 4.65 mmol/L in all arterial blood gas analyzed. Despite these correction factors, we found significant p50 temporal changes in critically ill COVID-19 patients with negative outcome, which we have analyzed and reported as an interesting mechanism never previously analyzed in critically ill COVID-19 patients (late p50s 23.0 ± 1.6 mmHg in alive patients vs. 33.1 ± 7.9 mmHg in dead patients, p < 0.01).…”
mentioning
confidence: 99%
“…Very recently Ceruti et al, published an interesting article about “Temporal Changes in the Oxyhemoglobin Dissociation Curve of Critically Ill COVID-19 Patients“ [ 1 ]. Similar to Vogel et al in 2020 [ 2 ], they found a low standard half saturation pressure P 50 in patients undergoing invasive mechanical ventilation which decreased more during the subsequent days in patients with a good prognosis.…”
mentioning
confidence: 99%
“…In Figure S2 (Supplementary Materials) [ 1 ], the authors compare the P 50 calculated with the Hill equation according to Severinghaus [ 5 ] and with the Dash equations [ 3 ]. While the difference is small (maximally 2mm Hg) or even negligible above 16% saturation, the Dash values dramatically decrease at lower saturations.…”
mentioning
confidence: 99%